2015
DOI: 10.1016/j.cryobiol.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells derived from various tissues: Biological, clinical and cryopreservation aspects

Abstract: Originally isolated from bone marrow, mesenchymal stromal cells (MSCs) have since been obtained from various fetal and post-natal tissues and are the focus of an increasing number of clinical trials. Because of their tremendous potential for cellular therapy, regenerative medicine and tissue engineering, it is desirable to cryopreserve and bank MSCs to increase their access and availability. A remarkable amount of research and resources have been expended towards optimizing the protocols, freezing media compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
234
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(251 citation statements)
references
References 203 publications
4
234
0
3
Order By: Relevance
“…Several studies have shown that successful cryopreservation of cells in suspension needs suiciently high cooling rates to reach quickly low temperatures and avoid slow-cooling injury, but low enough cooling rates to decrease the formation of intracellular ice and avoid rapid-cooling injury [51]. The responses to cooling rates are cell-type speciic, as distinct cell types have diferent membrane permeability parameters.…”
Section: Freezingmentioning
confidence: 99%
“…Several studies have shown that successful cryopreservation of cells in suspension needs suiciently high cooling rates to reach quickly low temperatures and avoid slow-cooling injury, but low enough cooling rates to decrease the formation of intracellular ice and avoid rapid-cooling injury [51]. The responses to cooling rates are cell-type speciic, as distinct cell types have diferent membrane permeability parameters.…”
Section: Freezingmentioning
confidence: 99%
“…There have been several reports of mesenchymal stromal cells for expansion and cryopreservation for clinical applications, such as in graft versus host disease [60], but the product potency has come into question [61] and cryopreservation was one of the steps under scrutiny. Further detailed studies indicated a range of reversible and non-reversible effects of cryopreservation in mesenchymal stromal cells using slow cooling with a range of DMSO concentrations and cell pre-treatments [62]. Post-thaw culture for 24 h was found to be effective in reparation of many of the cryo-induced abnormalities.…”
Section: Historical and Current Cell Therapy Cryopreservationmentioning
confidence: 99%
“…Cryoprotectants are classiied into permeating and non-permeating agents depending on their ability to cross the cell membrane [11,12]. The permeating cryoprotectants, such as dimethyl sulphoxide (DMSO), are used for clinical preservation and banking of MSCs for the treatment of graft-versus-host disease (GVHD) [13]. The International Stem Cell Initiative (ISCI) recommends the use of dry shippers involving liquid nitrogen (-196°C) for frozen stem cell transportation [2].…”
Section: Temperature Stabilisationmentioning
confidence: 99%